The Reality of the Implementation of Computer Teachers for Innovation Environment Specification for Secondary School in Riyadh - Al-Humud, Seham Mohammed (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the reality of the Implementation of computer teachers for Innovation Environment Specification for secondary school in Riyadh, and to identify whether the Implementation of computer teachers differs according to qualification variables and years of experience. To achieve this, the descriptive survey method was used, and the study was applied to a sample of (50) secondary school computer teachers in the Riyadh region.The study reached the following results: the reality of the Implementation of computer teachers to the innovative classroom environment related to classroom activities was high with a general average of (2.65), and the reality of the Implementation of computer teachers to the innovative classroom environment related to teaching methods was high with a general average of (2.56), and the reality of the Implementation of computer teachers to the innovative classroom environment related to the evaluation was high with a general average of (2.73), and the reality of the Implementation of computer teachers to the innovative classroom environment related to classroom management was high with a general average of (2.89). The results also indicated that there were no statistically significant differences in the application of computer teachers for secondary school in Riyadh to the innovative classroom environment, according to educational qualifications and years of experience. The study came out with a number of recommendations, including making use of the list of innovative classroom environment specifications to preparing training programs for computer teachers and supervisors, and intensifying professional development programs offered to teachers and supervisors with the importance of applying the innovative classroom environment.
Keywords: Innovation Environment; computer teachers; Curriculum Theories